Color Impulse Therapy in the Complex Rehabilitation of Patients with Tension-Type Headache, Insomnia and Associated Anxiety Disorders (International Journal of Psychosocial Rehabilitation, 2020)
The present article describes the results of the clinical studies and the rehabilitation of patients with a tension-type headache and/or insomnia. The rationale for the present study is explained by the high rate of this pathology among the population and the need for the development of new, more effective methods of treatment of this pathology. The evaluation of the effectiveness of the complex approach to the rehabilitation of patients using the non-invasive apparatus technology and methods of osteopathic correction was performed. The main methods of the study were visual color impulse therapy by means of the apparatus APC-01U (“MedTechProCor,” Russia) along with the binaural therapy and osteopathic correction, which allowed the authors to evaluate the efficiency of this complex treatment. The performed tests showed that the patients’ general health, mood, and quality of life improved. The pain syndrome was relieved, the blood circulation rate in the brachiocephalic vessels increased, the level of anxiety decreased, and the quality of sleep improved. The materials of the article can be useful for doctors that use unconventional methods of treatment for patients with psychosomatic and ophthalmologic diseases, neurologists, and psychotherapists.